DETERMINANTS OF EQUITY MUTUAL FUND PERFORMANCE: EMPIRICAL EVIDENCE FROM THAILAND - PANROT, Thidatip; เห็นสว่าง, สุรางค์; เลาหวิเชียร, ทิพย์รัตน์; สิริวัฒน์ธนกุล, ธนาวัฒน์ (Thai Interdisciplinary and Sustainability Review, 2025)
This article investigates the determinants of equity mutual fund performance in Thailand, using data from 300 funds listed on the Stock Exchange of Thailand between 2020 and 2022. Multiple regression analysis reveals that certain financial ratios, such as the total asset turnover ratio and return on assets, are positively related to fund performance. In contrast, the debt-to-asset ratio is negatively related. Additionally, fund size and manager characteristics, such as education, experience, and qualifications, have a positive impact on performance as measured by the Sharpe Ratio and Jensen's Alpha. Finally, stock selection and market timing abilities significantly and positively affect fund performance. These findings are beneficial for fund managers, investors, and regulators in making investment decisions and developing strategies to enhance returns and sustainability.